High Physiological Omega-3 Fatty Acid Supplementation Affects Muscle Fatty Acid Composition and Glucose and Insulin Homeostasis in Obese Adolescents. (20th February 2012) - Dangardt, Frida; Chen, Yun; Gronowitz, Eva; Dahlgren, Jovanna; Friberg, Peter; Strandvik, Birgitta
Abstract : Obese adolescents have high concentrations of saturated fatty acids and low omega-3 long-chain polyunsaturated fatty acids (LCUFAs) in plasma phospholipids. We aimed to investigate effects of omega-3 LCPUFA supplementation to obese adolescents on skeletal muscle lipids and glucose and insulin homeostasis. Twenty-five obese adolescents (14–17 years old, 14 females) completed a randomized double-blind crossover study supplying capsules containing either 1.2 g omega-3 LCPUFAs or placebo, for 3 months each with a six-week washout period. Fasting blood glucose, insulin, leptin, adiponectin, and lipids were measured. Intravenous glucose tolerance test (IVGTT) and euglycemic-hyperinsulinemic clamp were performed, and skeletal muscle biopsies were obtained at the end of each period. The concentrations of EPA, DHA, and total omega-3 PUFA in muscle phospholipids increased in both sexes. In the females, omega-3 LCPUFA supplementation improved glucose tolerance by 39% (P = 0.04 ) and restored insulin concentration by 34% (P = 0.02 ) during IVGTT. Insulin sensitivity improved 17% (P = 0.07 ). In males, none of these parameters was influenced by omega-3 supplementation. Thus, three months of supplementation of omega-3 LCPUFA improved glucose and insulin homeostasis in obese girls without influencing body weight.